CT and IQ in HIV Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Measures of cognitive function and social-emotional behavior were correlated with CT abnormalities in 87 children with symptomatic human immunodeficiency virus type 1 disease (HIV) at the Pediatric Branch, National Cancer Institute, and the NIND & S, Bethesda, MD; Children's National Medical Center, Washington, DC; and Medical Illness Counselling Center, Chevy Chase, MD.